Schistosoma mansoni: the sex ratios of worms in animals infected with cercariae from three species of Biomphalaria Schistosoma mansoni: relação de vermes machos e fêmeas em animais inoculados com cercárias de três espécies de Biomphalaria - Cecília Pereira de Souza; Liana K. Jannotti-Passos; Sueleny Silva Ferreira; Iaci Belo de Figueiredo Vieira (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
The ratios of male to female worms of Schistosoma mansoni were determined in mice infected with cercariae from LE, SJ and AL strains shed by mollusc hosts of the parasite in Brazil. The sex ratios of worms in the animals were similar with cercariae from Biomphialaria glabrata and B. tenagophila varying from 1.1:1 to 1.6:1 with LE and AL strains and 1:1.1 with SJ. In the animals infected with cercariae from B. straminea the ratio of male to female worms was similar to those obtained using cercariae shed from the other two species of molluscs, 1.5:1 with LE strain. Inoculations by AL and SJ cercariae resulted in sex ratios of 3.1:1 and 6:1 respectively. The normal sex ratios of worms established in Brazil in animals inoculated with cercariae from B. glabrata and B. tenagophila is from 1:1 to 2:1. The higher number of male worms that developed from cercariae of the AL and SJ strains obtained from B. straminea indicate a lower compatibility of the snail concerning these strains of S. mansoni. A relação de vermes machos e fêmeas de Schistosoma mansoni foi determinada em camundongos infectados com cercárias das cepas LE, SJ e AL, eliminadas pelos moluscos hospedeiros do parasita no Brasil. Os números de vermes machos e fêmeas recuperados em inoculações de cercárias provenientes de Biomphalaria glabrata e B. tenagophila, foram semelhantes, variando de 1,1:1 a 1,6:1 com LE e AL e de 1:1,1 com SJ. Nos animais inoculados com cercárias provenientes de B. straminea a relação de vermes macho e fêmea foi semelhante à obtida com cercárias provenientes das outras duas espécies com a cepa LE, relação de 1,5:1. Nas inoculações de cercárias de AL e SJ provenientes de B. straminea a relação foi de 3,1:1 e 6:1, respectivamente. A relação normal de vermes macho para fêmea registrada no Brasil, em inoculações de cercárias de B. glabrata e B. tenagophila, é de 1:1 a 2:1. O grande número de vermes machos provenientes de cercárias das cepas AL e SJ eliminadas por B. straminea mostrou a compatibilidade menor do molusco com essas cepas de ...